2015
DOI: 10.4238/2015.december.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Mutational characterization of the P3H1/CRTAP/CypB complex in recessive osteogenesis imperfecta

Abstract: ABSTRACT. Osteogenesis imperfecta (OI) is a genetic disease characterized by bone deformities and fractures. Most cases are caused by autosomal dominant mutations in the type I collagen genes COL1A1 and COL1A2; however, an increasing number of recessive mutations in other genes have been reported. The LEPRE1, CRTAP, and PPIB genes encode proteins that form the P3H1/CRTAP/CypB complex, which is responsible for posttranslational modifications of type I collagen. In general, mutations in these genes lead to sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…In a similar study, our group also analyzed LEPRE1, CRTAP, and PPIB genes and the results have already been published (Barbirato et al, 2015).…”
Section: Molecular Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar study, our group also analyzed LEPRE1, CRTAP, and PPIB genes and the results have already been published (Barbirato et al, 2015).…”
Section: Molecular Analysismentioning
confidence: 99%
“…This study was approved by the Research Ethics Committee of the HINSG and informed consent was obtained from all participants (Barbirato et al, 2015).…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants gave informed consent to participate in this study. Fifteen patients previously described by our group (Barbirato et al , 2009, 2015, 2016; Moraes et al , 2012) were re-analyzed in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Fragments with abnormal patterns on SSCP gels were analyzed after silver staining, and Sanger sequencing was performed in an ABI PRISM® 3100 Genetic Analyzer (Applied Biosystems, USA). The primers used for the COL1A1 gene were previously described by Körkkö et al (1998); those used for P3H1 , CRTAP and PPIB were reported by Barbirato et al (2015). The primers for COL1A2 , SERPINF1 , SERPINH1 , FKBP10, WNT1 and IFITM5 are described in the -.…”
Section: Methodsmentioning
confidence: 99%